2015
DOI: 10.1186/s40712-015-0039-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aging at room temperature on hydrogen embrittlement behavior of Ni-Ti superelastic alloy immersed in acidic fluoride solution

Abstract: Background: It is important to investigate the mechanism for the hydrogen embrittlement of Ni-Ti superelastic alloy in acidic fluoride solutions so that the reliability and safety of the alloy as a dental device can be improved. The purpose of the present study is to investigate the effect of aging at room temperature on the hydrogen embrittlement behavior of Ni-Ti superelastic alloy immersed in acidic fluoride solution. Methods: Specimens were immersed separately in 50 mL of 0.2 % acidulated phosphate fluorid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…Yamabe et al [34], Fujiwara et al [35], and Simmons et al [36] tested elastomeric sealing material NBR at room temperature, 30 • C, and 110 • C, and found that there is no hydrogenation or structural activity below 30 • C, but at 110 • C, compression set is increased by 40%, which indicates that with increasing temperature, the elastomeric sealing materials show a thermal aging tendency. Menon et al [37], Castagnet et al [38], and Klopffer et al [39] tested different types of thermoplastic polymeric sealing materials at room temperature and 20-80 • C, respectively, and observed some random behavior. The degree of crystallinity can be increased with increasing temperature, but mechanical properties do not change.…”
Section: A Laboratory Test For Thermal Agingmentioning
confidence: 99%
See 3 more Smart Citations
“…Yamabe et al [34], Fujiwara et al [35], and Simmons et al [36] tested elastomeric sealing material NBR at room temperature, 30 • C, and 110 • C, and found that there is no hydrogenation or structural activity below 30 • C, but at 110 • C, compression set is increased by 40%, which indicates that with increasing temperature, the elastomeric sealing materials show a thermal aging tendency. Menon et al [37], Castagnet et al [38], and Klopffer et al [39] tested different types of thermoplastic polymeric sealing materials at room temperature and 20-80 • C, respectively, and observed some random behavior. The degree of crystallinity can be increased with increasing temperature, but mechanical properties do not change.…”
Section: A Laboratory Test For Thermal Agingmentioning
confidence: 99%
“…This reaction causes permanent changes in structure, composition, and morphology. In this method, materials remain in contact with different chemicals, mostly immersed in the solution and charged with hydrogen [36,37,40,41]. This type of aging is frequently seen by both storage and sealing materials due to their continuous interaction with chemicals.…”
Section: Chemical Agingmentioning
confidence: 99%
See 2 more Smart Citations
“…However, during the production stages, hydrogen absorption occurs frequently during acid washing and electropolishing processes [7]. This fact may be critical since it has been often reported that the contamination of hydrogen can lead to several detrimental effects such as: (1) suppression of martensitic phase transformation [8][9][10][11][12], (2) noticeable increase of the transformation stress threshold [7,8,10,11,13,14] and (3) embrittlement [7,10,13,[15][16][17][18]. Recently, Duerig et al [19] have pointed out several aspects of hydrogen in Ni-Ti and highlighted both localized and highly dynamic effects.…”
Section: Introductionmentioning
confidence: 99%